Vaccines for contagious diseases - Liew Oi Leng, Irene; Toh, Hwee Ting; Mohammed, Elizah; Mohd Fauzi, Noor Akhmazillah (Penerbit UTHM, 2022)
Vaccination against contagious diseases which greatly decreases the mortality rate and promotes population health is a valuable invention in medical biotechnology. With the improvements made in biotechnology, the production and effectiveness of vaccines also experience an advancement from the commonly applied recombinant DNA technology to the reverse genetics’ techniques and newly DNA vaccines which is still not common in the applications for humans. The application of biotechnologies in the vaccine preparation process greatly helps to save the time and expenses spent and many possible preventive measures with higher efficiency or new vaccines are discovered with the help of biotechnology applied. Breakthrough in prevention against antibiotic resistance bacteria or challenging diseases contribute to the development of the medical field. However, the rapid growth of biotechnology and their application in vaccination also raise the awareness of the public regarding the ethical and safety issues such as biological weapons and vaccine scares. Authorities should put in more efforts to overcome these challenges to maximize the benefits of vaccination to humans especially in preventing the deadly contagious diseases outbreaks in the world.